Health and economic development: Evidence from the introduction of public health care - Anthony Strittmatter; Uwe Sunde (Institute for the Study of Labor (IZA), 2011)
This paper investigates the causal effect of changes in health on economic development using a long panel of European countries. Identification is based on the particular timing of the introduction of public health care systems in different countries, which is the random outcome of a political process. We document that the introduction of public health care systems had a significant immediate effect on the dynamics of infant mortality and crude death rates. The findings suggest that a reduction in infant mortality or crude death rates exhibited a positive effect on growth in income per capita and increased population growth.
urn:nbn:de:101:1-201108152082
Keywords: I10; J10; O11; N13; 330; mortality; economic development; growth; public health care